Analysis of the distribution characteristics and influencing factors of viruses carried by atmospheric PM2.5 based on metaviromics - Wenli Wang; Yongxin Wang; Haoneng Hu; Quan Zhou; Shuling Kang; Yu Jiang; Jianjun Xiang; Jing Wu; Jing Li; Zhiwei Chen; Chuancheng Wu (Frontiers in Public Health, 2025)
BackgroundFine particulate matter (PM2.5) is a well-known air pollutant and has been suggested as a potential vector for airborne viruses, raising public health concerns. This study employed metaviromic sequencing to systematically analyze the composition, temporal–spatial distribution, and environmental influencing factors of viral communities in PM2.5 samples collected from Fuzhou, China, to identify potential high-risk viruses and the key factors influencing their presence.MethodsThree outdoor PM2.5 sampling sites were established in the city center, rural–urban fringe, and rural areas of Fuzhou. Samples were collected from December 2022 to August 2023. The collected PM2.5 samples underwent high-throughput sequencing and viral annotation, and statistical analysis along with multivariate regression analyses were used to investigate the characteristics of viral distribution and its influencing factors.ResultsA total of 117 PM2.5 samples were collected. The viral community diversity in PM2.5 exhibited significant seasonal variation (p < 0.05), with the highest number of viral species detected in winter at both the genus and species levels. In terms of regional distribution, the highest number of viruses was found in city center and the lowest in rural areas, while there were slight differences in viral composition among regions, these were not statistically significant. Additionally, analysis of environmental factors revealed that sulfur dioxide (SO2) in the air quality factor and wind speed in the meteorological factor influenced the relative abundance of viruses.DiscussionUrbanization and human activities may affect regional viral patterns, but the overall improved air quality in Fuzhou could have reduced regional disparities. Environmental factors such as SO2 and wind speed may influence viral survival and dispersion, suggesting that non-traditional pollutants warrant closer attention in the context of airborne virus transmission.